2017
DOI: 10.1016/j.powtec.2016.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Production of fine calcium powders by centrifugal atomization with rotating quench bath

Abstract: Recently, a novel Al/Ca composite was produced by severe plastic deformation of Al powders and Ca granules for possible use as a high-voltage power transmission conductor. Since the strength of such composites is inversely proportional to the Ca filament size, fine Ca powders (less than ~250 μm) are needed to achieve the desired high strength for the powder metallurgy production of an Al-matrix composite reinforced by nano-scale Ca filaments. However, fine Ca powders are not commercially available. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Tian et al [13,16,31] studied the microstructure strength relation in Al-Ca composites and found that the strength value 476 MPa of Al-20 vol% Ca composite is four times higher than the predicted strength by the rule of mixtures of pure Al and Ca. [32,33] The Al-Ca composite processed by power metallurgy [34] and severe plastic deformation (as demonstrated in Figure 1), has a high strength, [25] high electrical conductivity [16,35] that is ideal for a high voltage power transmission electrical conductor. [36,37] Trybus and Spitzig [38] studied a rolled and wire-drawn Cu-Nb composite.…”
Section: Heterophase Interface In a Metal-compositementioning
confidence: 99%
See 1 more Smart Citation
“…Tian et al [13,16,31] studied the microstructure strength relation in Al-Ca composites and found that the strength value 476 MPa of Al-20 vol% Ca composite is four times higher than the predicted strength by the rule of mixtures of pure Al and Ca. [32,33] The Al-Ca composite processed by power metallurgy [34] and severe plastic deformation (as demonstrated in Figure 1), has a high strength, [25] high electrical conductivity [16,35] that is ideal for a high voltage power transmission electrical conductor. [36,37] Trybus and Spitzig [38] studied a rolled and wire-drawn Cu-Nb composite.…”
Section: Heterophase Interface In a Metal-compositementioning
confidence: 99%
“…[87] The high purity (99.5%) Ca metal powders (106-212 mm) were produced by a unique centrifugal atomization system with rotating quench bath developed at Ames Laboratory. [34] The powders (80 vol%, 157 g Al powders and 20 vol%, 22.4 g Ca powders) were mixed in a TURBULA Shaker-Mixer and then die pressed into cylindrical powder compacts with a relative density of 65% under 40.6 MPa pressure. This compaction pressure and green density matched the compressibility curve for gas atomized Al powders.…”
Section: Extrusion Based Bondingmentioning
confidence: 99%
“…The previously described atomization of Gd powder was performed in the Ames Laboratory RDA with an expanded quench bath from what is referenced by Tian et. al [11]. Before this expansion, atomization of rare earth metals under similar run conditions but with a 40% smaller quench bath diameter produced 30-50% flake in the 150-250µm size range.…”
Section: Powder Yieldmentioning
confidence: 96%
“…al. [11], and was modified for production of rare earth powders. The system is enclosed to provide vacuum capability that can be backfilled with an argon atmosphere essential to preventing oxidization of the rare earth charge material.…”
Section: 1mentioning
confidence: 99%
“…An alternative approach for melt granulation is melt centrifugal atomization (MCA), in which a centrifugal force is employed to stretch the melt jet into molten droplets, which immediately solidify into spherical granules [7]. As a one-step and high-throughput approach to prepare uniform spherical granules, MCA has been used in the field of metal granule preparation [8].…”
Section: Introductionmentioning
confidence: 99%